Finding An Alternative Routing For Solid Waste Management - Manoharam, Gaeithry (Pusat Pengajian Sains Matematik, 2020)
Finding the shortest route for transferring solid waste is one of the biggest challenges for every solid waste management organization. Globally, waste collection process represents 74% of operating costs, yet it has been given minor attention. In this research, Dijkstra Algorithm and Travelling Salesman Problem (TSP) using GIS Software 10.1 were used to optimize the route from Seberang Perai Industrial area to Ampang Jajar waste transfer station. Using the technique, we compare the existing and optimized route with the 24 companies from phases I, II and IV in the Seberang Perai Industrial area to waste transfer stations. Dijkstra and TSP are some of the classic algorithms in the GIS which are used to find the shortest route to reduce the operating cost. Carbon emission is an extended part of this study by comparing transportation fuel consumption between existing routes and optimized routes.